2021
DOI: 10.1177/23312165211007367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronological Age on Pulse Rate Discrimination in Adult Cochlear-Implant Users

Abstract: Cochlear-implant (CI) users rely heavily on temporal envelope cues to understand speech. Temporal processing abilities may decline with advancing age in adult CI users. This study investigated the effect of age on the ability to discriminate changes in pulse rate. Twenty CI users aged 23 to 80 years participated in a rate discrimination task. They attempted to discriminate a 35% rate increase from baseline rates of 100, 200, 300, 400, or 500 pulses per second. The stimuli were electrical pulse trains delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 92 publications
(154 reference statements)
0
6
0
Order By: Relevance
“…Temporal processing deficits observed in elderly CI users can be attributed to both central (e.g., Moberly et al 2017, 2018; Johnson et al 2021) and peripheral mechanisms. At the peripheral level, results of human temporal bone studies showed that neural damage, including loss of spiral ganglion neurons (SGNs) and peripheral axons of AN fibers, is the major characteristics of age-related hearing loss (Schuknecht & Gacek 1993; Viana et al 2015; Wu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Temporal processing deficits observed in elderly CI users can be attributed to both central (e.g., Moberly et al 2017, 2018; Johnson et al 2021) and peripheral mechanisms. At the peripheral level, results of human temporal bone studies showed that neural damage, including loss of spiral ganglion neurons (SGNs) and peripheral axons of AN fibers, is the major characteristics of age-related hearing loss (Schuknecht & Gacek 1993; Viana et al 2015; Wu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, psychophysical measures were conducted using long-duration pulsatile stimulation. In contrast, the AN function was quantified based on either the slope of the eCAP input/output function (Shader et al 2020a(Shader et al , 2020bJohnson et al 2021) or the time constant estimated based on the eCAP HE ET AL. / EAR & HEARING, VOL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abilities are as good as 3 to 7% for rates of ~ 100 Hz, but performance declines rapidly for rates > 200–300 Hz (e.g., Carlyon and Deeks 2002 ; Carlyon et al 2008 ; Kong et al 2009 ; Macherey and Carlyon 2014 ). The physiological basis for this limitation on rate discrimination may arise from both peripheral and central sources (e.g., Ihlefeld et al 2015 ; Johnson et al 2021 ). Previous studies have demonstrated age-related declines in rate discrimination (DeVries et al 2022 ; Gaskins et al 2019 ) and in other temporal processing tasks, including gap detection (Snell 1997 ), duration discrimination (Fitzgibbons and Gordon‐Salant 1995 ), and tempo discrimination (Fitzgibbons and Gordon-Salant 2001 ).…”
Section: Introductionmentioning
confidence: 99%